LEARNING FOR GENDER EQUALITY IN POST-INDUSTRIAL ECONOMY: AN ONLINE PROGRAM OVERVIEW - Usca, Svetlana; Mykhailenko, Olena; Abuze, Anda; Vindaca, Olga; Desyatnyuk, Oksana (Education Reform: Education Content Research and Implementation Problems, 2021)
The Latvian – Ukrainian project "Gender aspects of digital readiness and development of human capital in region" Nr.LV-UA/2018/3 focuses on the digitalization of education for closing the gender employment gap in the profoundly transforming labour market.The article focuses on the online program "Learning for Gender Equality in Post-Industrial Economy" for professional development of educators. The program grounds on research previously done at the project. In this article, we review the program content and provide an evaluation of its participants.